Genetic Variation of PD-L1 Gene Affects its Expression and Is Related to Clinical Outcome in Epithelial Ovarian Cancer - Sun, Haiyan; Li, Yan; Si, Wengang; Hua, Tian; Chen, Juan; Kang, Shan (Frontiers in Oncology, 2022)
Objective: This study aims to investigate the effect of polymorphisms of programmed cell death-ligand 1 (PD-L1) on the risk and patient's outcomes of epithelial ovarian cancer (EOC). Methods: Totally, 568 patients and 532 healthy women were included. Three polymorphisms in the PD-L1 gene, rs2297136, rs4143815 and rs4742098, were genotyped by the polymerase chain reaction/ligase detection reaction (PCR-LDR). Survival analysis was performed in 234 patients (received primary debulking surgery followed by platinum-based chemotherapy). Results: Patients with the rs2297136 AG + GG genotypes had shorter progression-free survival (PFS) (hazard ratio (HR)=1.44, 95% CI=1.03-2.01) and overall survival (OS) (HR=1.55, 95% CI=1.06-2.27) than those with the AA genotype. Moreover, the mRNA and protein expression levels of PD-L1 in EOC tissues with the rs2297136 AG + GG genotypes were remarkably higher than those with the AA genotype (P=0.032 and P=0.047, respectively). Survival analysis showed that high expression of PD-L1 mRNA was remarkably associated with worse 10-year PFS (HR=1.55, 95% CI=1.28-1.88) and OS (HR=1.51, 95% CI=1.00-2.28) in EOC patients. Conclusions: The rs2297136 may not only effectively influence the expression of PD-L1, but also is significantly associated with EOC patients' outcomes.